Network architecture of internet backhaul by DVB-RCS standards for shipborne and other mobile applications - Stojce Ilcev, Dimov (International Journal of Engineering and Technology, 2020)
In this paper is introduced a new Digital Video Broadcasting-Return Channel via Satellite (DVB-RCS) for the implementation of modern satellite Internet for shipborne, Vehicleborne and airborne mobile applications via Geostationary Erath Orbit (GEO) satellites. Mobile Satellite Internet aims at providing the next generation satellite broadcasting service through C, Ku and Ka-band DVB-S2 standard for Mobile Earth Stations (MES) via GEO satellite and Land Earth Stations (LES) to the ground or other mobile subscribers. It is de facto a mobile interactive broadcast satellite access system, which provides both TV broadcasting and high-speed Internet broadband based on DVB-S/DVB-RCS standards, Internet Protocol (IP) network, World Wide Web, IPTV, E-solutions and Communication, Navigation and Surveillance (CNS) systems to the passengers and crews onboard ships, land and aeronautical vehicles.Â Â